2022
DOI: 10.3389/fpls.2022.903661
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Agronomic Performance of Lupinus mutabilis Germplasm in European and Andean Environments

Abstract: The introduction of Lupinus mutabilis (Andean lupin) in Europe will provide a new source of protein and oil for plant-based diets and biomass for bio-based products, while contributing to the improvement of marginal soils. This study evaluates for the first time the phenotypic variability of a large panel of L. mutabilis accessions both in their native environment and over two cropping conditions in Europe (winter crop in the Mediterranean region and summer crop in North-Central Europe), paving the way for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Even though PCoA1 and PCoA2 explained only 17.63% of the total genetic variance, this grouping corroborates previous findings. A similar separation pattern within this GWAS panel was already inferred from phenotypic observations (Gulisano et al, 2022) and is now confirmed in a genomic relationship matrix based on genotype information for each individual marker (VanRaden, 2008).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Even though PCoA1 and PCoA2 explained only 17.63% of the total genetic variance, this grouping corroborates previous findings. A similar separation pattern within this GWAS panel was already inferred from phenotypic observations (Gulisano et al, 2022) and is now confirmed in a genomic relationship matrix based on genotype information for each individual marker (VanRaden, 2008).…”
Section: Resultssupporting
confidence: 84%
“…The broad variation in yield and composition of biomass encountered in the GWAS panel confirms the high potential of germplasm collections as important breeding resources for the improvement of biomass quality. Large ranges of variation in biomass yield across environments can be attributed to the effect of different environmental conditions on L. mutabilis development (Gulisano et al, 2022). This is confirmed by the dissection of phenotypic variation for biomass components across trials which sees the effect of the environment as the largest on these traits (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced representation sequencing and single nucleotide polymorphism (SNP) typing was performed as previously described in Gulisano et al (2022a). Briefly, genomic DNA was isolated from young grinded L. mutabilis leaves (∼20-400 mg, freeze dried material) using acetyl trimethyl ammonium bromide (CTAB) method (Doyle and Doyle, 1987) as described in Petit et al (2020).…”
Section: Genotyping and Snp Developmentmentioning
confidence: 99%